Dinâmica metropolitana, vulnerabilidade socioambiental e sua interface com as mudanças climáticas na região metropolitana de Natal/RN - Alves, Edilza Paula Queiroz (2019)
The expansion of the cities brought with it the problem of disorder in the urban centers caused by the process of urbanization and population growth, which reflected in its metropolitan dynamics and its socio-spatial organization, accompanied by social and territorial inequalities, contributing to segregated spaces by the population in situation of socio-environmental vulnerability, resulting in impacts on the soil, due to their misuse and occupation. Thus, the Metropolitan Region of Natal (MRN) was marked by major changes in the organization of its space, in its socioeconomic activities, the way of living and inhabiting in urban spaces, the degradation of the soil, showing factors that can cause changes in climate change. In this sense, the present research aimed to understand how the dynamics of the MRN socio-spatial organization at its intrametropolitan level integrates the perspective of climate adaptation and risk management in their territories. The methodological procedures used follow the guidelines of a qualitative and quantitative research, through bibliographic reviews and data collection instruments. As source it was used the microdata from the 2010 Demographic Census and the Survey of Basic Municipal Information (MUNIC-2017), both from IBGE, and the 2010 Social Vulnerability Atlas (IVS) presented by IPEA. The results show that the MRN’s socio-spatial organization is unequal, being the result of socio-economic factors that reflect urban and climatic changes in a context of socio-environmental vulnerability. Therefore, strategies are needed to deal with the reduction of risks caused by climate changes.